Detekce graffiti tagů v obraze - Pavlica, Jan (Vysoké učení technické v Brně. Fakulta informačních technologií, 2017)
Tato práce se zaměřuje na možnost využití současných metod v oblasti počítačového vidění za účelem automatické detekce graffiti tagů v obraze. Tagy jsou nejčastějším projevem graffiti, který slouží jako podpis autora. V rámci práce byly otestovány state-of-art detekční systémy, z nichž se nejvíce osvědčil Single Shot MultiBox Detector. Bylo u něj dosaženo 75,7% AP.

The thesis is focused on the possible utilization of current methods in the area of computer vision with the purpose of automatic detection of graffiti tags in the image. Graffiti tagsare the most common expression of graffiti, which serves as the author’s signature. In the thesis, state-of-the-art detection systems were tested; the most effective one is the Single Shot MultiBox Detector. The result has reached 75.7% AP.
Detection of Graffiti Tags in Image
Keywords: graffiti tagy; detekce objektů; konvoluční neuronové sítě; YOLOv2; Tiny YOLO; You Look Only Once; SSD; Single Shot MultiBox Detector; Faster R-CNN; graffiti tags; object detection; convolutional neural networks; YOLOv2; Tiny YOLO; You Look Only Once; SSD; Single Shot MultiBox Detector; Faster R-CNN